Directory of periodicals published in India, 2000 - Susheel Kaur (Comp.); Sapra, P (Comp.) (New Delhi Sapra and Sapra, 2000)
The Periodical Directory 2000 is more comprehensive, has additional new features for better access and use of serials information. It provides bibliographic informationon about 12,000 serials, 3000 more then previous edition and is arranged in six parts v
Keywords: Periodicals-Directories; Serial Publications; Newpapers-Directories